KEKERASAN DALAM RUMAH TANGGA Perspektif UU No. 23 Tahun 2004 Tentang PKDRT dan Hukum Islam - Pancasilwati, Abnan (Mazahib, 2013)
Domestic violence is one of the manifestations of violence that gender base and it is culture phenomenon that be constructed by many variables, among other, social system, culture, legal and religious beliefs. Gender injustice is a system and a structure in which both men and women are victims of the system. Domestic violence is born because of the relationship of husband-wife is hierarchical-structural, where the power relation between them are not unbalanced pattern, where unequal relationship that just gets juridical legitimation by the state, cultural and religious doctrine. Gender injustice manifested in various forms of injustice, namely marginalization, subordination stereotypes, violence, double burden, and the socialization of gender roles ideology that not equal. Therefore Â struggle to advocate for grounding principle of gender equality include three dimensions, namely efforts to reinterpretation legal subtances (positive and religion), build a culture community that gender sensitive and oversight of law enforcement officers.